Organelle interplay—peroxisome interactions in health and disease. Issue 1 (16th April 2019) - Schrader, Michael; Kamoshita, Maki; Islinger, Markus
Abstract: Peroxisomes are multifunctional, dynamic, membrane‐bound organelles with important functions in cellular lipid metabolism, rendering them essential for human health and development. Important roles for peroxisomes in signaling and the fine‐tuning of cellular processes are emerging, which integrate them in a complex network of interacting cellular compartments. Like many other organelles, peroxisomes communicate through membrane contact sites. For example, peroxisomal growth, positioning, and lipid metabolism involves contacts with the endoplasmic reticulum (ER). Here, we discuss the most recent findings on peroxisome‐organelle interactions including peroxisome‐ER interplay at membrane contacts sites, and functional interplay with mitochondria, lysosomes, and lipid droplets in mammalian cells. We address tether proteins, metabolic cooperation, and the impact of peroxisome interactions on human health and disease.